DAMPAK PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI HITAM (GLYCINE SOJA L.) VARIETAS MALIKA TERHADAP PEMBERIAN DOSIS ABU JANJANG KELAPA SAWIT PADA BERBAGAI JENIS TANAH - Sipayung, Patricius; Tarigan, Rio Stepanus; Ompusunggu, Magdalena (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
The objective of this study is to investigate the impact of oil palm bed ash at different doses on the growth and yield of black soybean plants (Glycine soja L.) in different types of soil. A Factorial Randomized Group Design (RAK) with two factors was used in this study. The first factor is the application of oil palm bed ash, a byproduct of burning palm fruit bunches. The second factor is the type of soil used in the experiment. The study's results indicate that andosol and alluvial soil types produce higher 100 seed weight, dry seed weight per plant, dry seed weight per plot, and number of pods per plot compared to ultisol soil and have a faster flowering age. However, these soil types have no significant effect on plant height, the number of productive branches, and plant root length. The combination of palm kernel ash and soil type had a significant effect on 100 seed weight, dry seed weight per plant, dry seed weight per plot, and number of pods per plot. However, this combination had no significant effect on plant height, flowering age, the number of productive branches, and root length. The largest dry seed weight per plot was observed in the K3M2 treatment combination at 78.25 g, and the smallest dry weight per sample was in the K0M1 treatment combination at 47.93 g. This resulted in a 30.32 g increase in dry seed weight per plot (63.27%). The utilization of palm kernel ash at a dosage of 375 g/polybag leads to a 34.26% increase in the dry seed weight per plant, a 30.20% increase in dry seed weight per plot, and a 42.06% increase in the number of pods per plot compared to plants without palm kernel ash application.